The Effect of Capital Expenditure and Investment on Income Inequality, - Jouzar Farouq Ishak; Amelia Rizky Alamanda; R.Wendi Rusmawan Kusumah (The Accounting Journal of Binaniaga, 2018)
The purpose of this study to give empirical evidence and examines theinfluence of capital expenditure and investment on income inequality at The SpecialAdministrative Region of Yogyakarta. The research objects are The SpecialAdministrative Region of Yogyakarta by considering pooled data and the samplingdesign as purposive sampling. The sampling here is confined to specific types ofpeople who can provide the desired information, either because they are the onlyones who have it, or conform to some criteria set by the researcher. This analysisuses multiple regression analysis is a statistical technique to predict the variance inthe dependent variable by regressing the independent variables against it. The resultof research shows that capital expenditure has no significant influence on incomeinequality in The Special Administrative Region of Yogyakarta, Investment has asignificant influence on income inequality in The Special Administrative Region ofYogyakarta, capital expenditure and investment simultaneously significant influenceon income inequality in The Special Administrative Region of Yogyakarta.